INFLUENCE MONITORING GEOTECHNICAL INSTRUMENTS AGAINTS PRELOADING WITH PREFABRICATED VERTICAL DRAIN (PVD) ON PEAT SOIL REVIEWED FROM TIME IMPLEMENTATION - OKTARIA, RANGGA PRIMA (KURVA S JURNAL MAHASISWA, 2017)
This resear chaims to know time of excecution of work and checking, identifying/ monitoring geotechnical instruments againts preloading of Prefabricated Vertical Drain (PVD) on peat soil, because of this type of soil has unstable nature againts land slide during preloading and cause a mis matches of time, volume and a high risk implementation, there fore conducted an analysis study to find out a condition and time implementation for next reference. This research was conducted by checking and surveying preloading with geotechnical monitoring instruments like inclinometer, settlement plate, pneumatic Piezometer and collect a necessary data. The analysis performed is quantitative or called statistical data analysis. It aims to determine the relationship between left and right of peat soil preloading pile.Time implementation based on geotechnical monitoring instrument (settlement plate) processed by mathematical comparison. Based on research, inclinometer analysis on preloading is = 5,99 > = 1,12335 and Coeffisien of Determination = 0,017316 = 1,73 %; settlement plate is = 5,99 > = 2,10095 dan ; Pneumatic Piezometer is = 13,7513 > = 2,100952 > = 5,99 and = 0,484 = 48,4 %. While time implementation of preloading Prefabricated Vertical Drain (PVD) summed up work planning = 528 days and realize = 547 days, Comparison of percentage = 3,5985 % from time schedulebut still in the scope of the work.